2001
DOI: 10.1106/hh4d-0ckm-j53x-fqk1
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of CFAST Predictions to USCG Real-Scale Fire Tests

Abstract: The zone model CFAST was used to make predictions of single room preflashover fire tests conducted in a steel enclosure. These results were then compared with previously published measurements obtained in fire tests. Tests included diesel pool fires, polyurethane slab fires, and wood crib fires. Half of these tests used natural ventilation (window, 1/4 door, and full door) while the remaining tests used forced ventilation (0.25 m3/s, 0.38 m3/s, and 0.61 m3/s). With the exception of heat release rates, all CFAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 16 publications
2
12
0
1
Order By: Relevance
“…Z i are also compared with CFAST 4.01 (e.g. [27]) predictions and the following smoke filling equations:…”
Section: Application For Big Hallsmentioning
confidence: 99%
“…Z i are also compared with CFAST 4.01 (e.g. [27]) predictions and the following smoke filling equations:…”
Section: Application For Big Hallsmentioning
confidence: 99%
“…The graphical comparisons can also be complemented with a quantitative number of the difference between the two sets of data. This was, for example, done in a comparison of CFAST predictions to real-scale compartment fire tests with natural and forced ventilation (Reneke and Peatross 2001) and it was found that the CFAST model over-predicted upper layer temperatures with less than 50°C. Another example is the modelling of the Dalmarnock fire tests (Rein et al 2011) where a posteriori simulations over-predicted the hot layer temperature by 10-50%.…”
Section: Fire Modelmentioning
confidence: 99%
“…Measuring positions of thermocouples trees (TF and TR) and concentration probes (CF and CR) and compartment size of experimental data. (3) 가 가장 대표적인 Filed 모델 코드로서 활용되고 있 으며, CFAST (4) 와 같은 Zone 모델 코드도 많이 활용되고 있 다. 최근에는 FDS와 같이 소스가 공개된 FireFOAM 코드 (5) 를 이용한 화재해석도 점차 증가하고 있다.…”
unclassified